HUBUNGAN FAKTOR KESEHATAN LINGKUNGAN TERHADAP KEJADIAN STUNTING UNTUK MENUNJANG SISTEM IMUN PADA BALITA DI PUSKESMAS SAWAH LEBAR TAHUN 2023 - Dewi, Devi Cynthia (Jurnal Sanitasi Profesional Indonesia, 2023)
The environmental health problems such as low sanitation and hygiene are likely to trigger any digestive disorders that will probably influence the number of nutritions received by the body. As a result, the body's resistance of children could be affected, and they will be vulnerable to infection. With this case, there is a higher risk of stunting in children. The major purpose of this study was to investigate the relationships between the environmental health and the occurrences of stunting in children under five years old in the area of Sawah Lebar Kota Bengkulu Health Center in 2023. The methodological approach taken in this research was observational analytic with a cross sectional approach. The samples of this research were 250 children under five years old. They were selected by using a purposive sampling technique. The univariate analysis and bivariate analysis was conducted by using a chi-square test. Based on the statistical analysis, the findings of this research indicated that there were significant influences of the drinking water sources (p=0.022), the quality of drinking water (p=0.006), the ownership of latrine (p=0.041), the waste management (p=0.000), and the hand washing habits p=0.002) on the occurrences of stunting. However, the variables such as the drinking water treatment (p=0.454) and the solid waste management (p=0.70) were apparent to have no significant influences on the occurrences of stunting in the area of Sawah Lebar Kota Bengkulu Health Center. Therefore, as implications of this research, it is expected for for health workers to provide socialization on practical and effective methods of sanitation and hygienic lifestyle. Hence, people could be aware on the importance of maintaining environmental health to avoid the occurrences of infectious diseases that could trigger the cases of stunting in children.